1992
DOI: 10.5144/0256-4947.1992.191
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Disorders in Saudi Children at the Al-Majardah General Hospital, Asir Region

Abstract: Saudi children with neurological disorders were seen at the Al-Majardah General Hospital, Asir Region. These constituted 7.5% of all the pediatric inpatients and outpatients. More than one-half of the children were under three years of age and 74% were six years and below. In the series, convulsive disorders accounted for 28.9% of cases, followed by cerebral palsy (18.9%), mental retardation (16.7%), infections (9.4%), trauma (8.9%), and disorders of the primary senses (6.7%). In 57% of the children, the lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…Febrile convulsions were not uncommon from the results of this study and the male excess conforms with the observation of other workers in Saudi Arabia as well as findings from other countries 7,25,26 . Although the prevalence rate in this study was similar to the figures reported from Guam, Italy and Sweden, it was however markedly lower than the figure of 9.4-136.2/1000 obtained in some other communities 1,26,27 .…”
Section: Discussionsupporting
confidence: 92%
“…Febrile convulsions were not uncommon from the results of this study and the male excess conforms with the observation of other workers in Saudi Arabia as well as findings from other countries 7,25,26 . Although the prevalence rate in this study was similar to the figures reported from Guam, Italy and Sweden, it was however markedly lower than the figure of 9.4-136.2/1000 obtained in some other communities 1,26,27 .…”
Section: Discussionsupporting
confidence: 92%
“…The 32 included studies were published between 1984 and 2020. Most of the studies were from Saudi Arabia ( n = 10) [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], Jordan ( n = 8) [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], Egypt ( n = 6) [ 47 , 48 , 49 , 50 , 51 , 52 ], and Iraq ( n = 4) [ 53 , 54 , 55 , 56 ]. Other studies were from Sudan ( n = 2) [ 57 , 58 ], Libya ( n = 1) [ 59 ], and Palestine ( n = 1) [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were a variety of study designs. Most were of case-series ( n = 13) [ 32 , 33 , 34 , 36 , 38 , 40 , 41 , 42 , 43 , 44 , 53 , 55 , 56 ] and cross-sectional design ( n = 11) [ 29 , 31 , 39 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Other study designs included: case-control ( n = 5) [ 35 , 54 , 58 , 59 , 60 ], retrospective review ( n = 2) [ 37 , 57 ], and prospective/retrospective cohort ( n = 1) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Izoura's and Anis' study (1992) from the Al Majarda area showed 28.9% of their cases were due to seizure disorders, 18.9% due to cerebral palsy and 16.7% were due to mental retardation. 11 Their relative lower frequencies for both the seizure disorders and mental retardation are possibly due to the fact that they have not included the cases of cerebral palsy, with either epilepsy or mental retardation, to the total percentage of each. However, there is no statistical difference in the frequency of most of the disorders between our study and theirs (P>0.05).…”
Section: Discussionmentioning
confidence: 99%